Bactobilin: blue bile pigment isolated from Clostridium tetanomorphum. - Brumm, P J (1983)
A blue bile pigment, possessing four acetic and four propionic acid side chains has been isolated from extracts of the anaerobic microorganism Clostridium tetanomorphum and in smaller amounts from Propionibacterium shermanii. The compound could be prepared in larger amounts by incubation of C. tetanomorphum enzyme extracts with added delta-aminolevulinic acid. The ultraviolet-visible, infrared, and proton magnetic resonance spectra of the pigment indicate a chromophore of the biliverdin type. Field-desorption mass spectrometry of the purified methyl ester showed a strong molecular ion at m/e = 962. This corresponds to the molecular weight expected for the octamethyl ester of a bilatriene type of bile pigment structurally derived from uroporphyrin III or I. Of the five possible structures, two could be eliminated by proton magnetic resonance spectroscopy. The name bactobilin is proposed for this previously unreported bile pigment.